Improving Mathematical Communication Skills Through the Geogebra-helped PBL and Direct Instruction Reviewed from the Level of Learning Independence - Hadi, Hadi; Wahyudin, Wahyudin; Usdiyana, Dian (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2024)
This research aims to analyze the improvement of junior high school students’ mathematical communication skills through Problem Based Learning (PBL) assisted by Geogebra and Direct Instruction assisted by Geogebra. The research also considers the level of student learning independence. The research method used was a quasi-experiment with a pretest-posttest design and a control group, involving two treatment groups. groups that underwent the PBL approach with the help of Geogebra and Direct Instruction with the help of Geogebra. Students in this study were divided based on their level of learning independence. Data was collected through an initial test (pretest), implementation of learning, and a final test (posttest). Data analysis involved a comparison between the increase in students’ mathematical communication skills before and after treatment in the two treatment groups, as well as the influence of the level of learning independence on increasing mathematical communication skills. The research results show that both learning approaches contribute to improving students’ mathematical communication skills. However, the group that took part in PBL assisted by Geogebra showed more significant improvement compared to the Direct Instruction group assisted by Geogebra. In addition, it was identified that the level of student learning independence influences the results of improving mathematical communication skills, where students with a high level of learning independence tend to benefit more from PBL assisted by Geogebra. In order to improve students’ mathematical communication skills in learning spatial material, it is recommended that educators consider using Geogebra-assisted PBL and pay attention to students’ level of learning independence in designing effective learning strategies. Â